A Numerical Analysis of an Innovative Flow Ripple Reduction Method for External Gear Pumps - Gianluca Marinaro; Emma Frosina; Adolfo Senatore (Energies, 2021)
In this paper, an innovative solution to minimize noise emission, acting on the flow ripple, in a prototype External Gear Pump (EGP) is presented. Firstly, a new tool capable to completely simulate this pump’s typologies, called EgeMATor, is presented; the hydraulic model, adopted for the simulation, is based on a lumped parameter method using a control volume approach. Starting from the pump drawing, thanks to different subroutines developed in different environments interconnected, it is possible to analyze an EGP. Results have been compared with the outputs of a three-dimensional CFD numerical model built up using a commercial code, already used with success by the authors. In the second section, an innovative solution to reduce the flow ripple is implemented. This technology is called Alternative Capacitive Volumes (ACV) and works by controlling and uniformizing the reverse flow, performing a consistent reduction of flow non-uniformity amplitude. In particular, a high reduction of the flow non-uniformity is notable in the frequency domain on the second fundamental frequency. The technology is easy to accommodate in a pump housing, especially for high-pressure components, and it helps with reducing the fluid-borne noise.